Failure to Replicate the Effects of the High-Probability Instructional Sequence on Feeding in Children With Autism and Food Selectivity. Issue 5 (September 2019) - Silbaugh, Bryant C.; Swinnea, Samantha
Behavioral intervention has positive effects on feeding problems of children with autism and food selectivity (FS), and researchers have evaluated a variety of specific behavioral interventions. Confidence in the effects of some specific interventions on feeding such as the high-probability instructional sequence (HPS) is limited by a lack of replication. Therefore, we assessed the generality of the HPS by replicating the intervention in children with autism and FS. Contrary to prior research, the HPS did not improve feeding responses for three consecutive children enrolled in the study. We discuss the results in relation to publishing failures to replicate without experimental control in applied behavior analysis research.